2010
DOI: 10.4311/jcks2009es0112
|View full text |Cite
|
Sign up to set email alerts
|

Fast, Regional Conduit Flow to an Exceptional-Value Spring-Fed Creek: Implications for Source-Water Protection in Mantled Karst of South-Central Pennsylvania

Abstract: Karst springs of Cumberland County, Pennsylvania, are important water resources, but their sources and flow paths are unknown. We traced flow in a mantledkarst groundwater system in the Great Valley section of the Valley and Ridge Physiographic Province using fluorescent dyes, with focus on Big Spring Creek. Upper Big Spring Creek is assigned High Quality/Exceptional Value status by Pennsylvania based on its high water quality and value as a multi-use resource with exceptional recreational or ecological signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Dye-tracing studies in these aquifers have shown that water can be transported from recharge areas to discharge areas miles away in days. (57) The ages shown in figure 4-1 likely pertain to the part of the carbonate-rock aquifer that is in the fractured rock without conduits, where flow tends to be slower than flow in conduits.…”
Section: Karst Features Make Carbonate Rock Aquifers Highly Susceptibmentioning
confidence: 99%
“…Dye-tracing studies in these aquifers have shown that water can be transported from recharge areas to discharge areas miles away in days. (57) The ages shown in figure 4-1 likely pertain to the part of the carbonate-rock aquifer that is in the fractured rock without conduits, where flow tends to be slower than flow in conduits.…”
Section: Karst Features Make Carbonate Rock Aquifers Highly Susceptibmentioning
confidence: 99%